2011
DOI: 10.1093/ndt/gfr528
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic beneficial effect of interleukin-1 inhibitor treatment in patients with familial Mediterranean fever complicated with amyloidosis and renal failure

Abstract: Anakinra has a strong effect on both inflammatory attacks and general status in patients with FMF-associated amyloidosis. It may contribute to changing the prognosis of these patients. Long-term studies are needed to appreciate the effect of anakinra or other IL-1 inhibitors on the natural history of amyloidosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 14 publications
1
36
0
2
Order By: Relevance
“…Anakinra is also given to other inflammatory or autoinflammatory diseases off-label. Familial Mediterranean Fever (FMF) is a hereditary chronic inflammatory disease which IL-1 plays a major role in, and blocking IL-1 reduces the symptoms [61, 62]. Anakinra was also shown to be effective in the case of nonhereditary chronic systemic inflammatory diseases like the adult-onset Still disease [63, 64], which involves arthritis, fever, and systemic inflammation or the childhood version—systemic-onset juvenile idiopathic arthritis (SJIA) [6567].…”
Section: Anti-inflammatory Cytokine Biologicsmentioning
confidence: 99%
“…Anakinra is also given to other inflammatory or autoinflammatory diseases off-label. Familial Mediterranean Fever (FMF) is a hereditary chronic inflammatory disease which IL-1 plays a major role in, and blocking IL-1 reduces the symptoms [61, 62]. Anakinra was also shown to be effective in the case of nonhereditary chronic systemic inflammatory diseases like the adult-onset Still disease [63, 64], which involves arthritis, fever, and systemic inflammation or the childhood version—systemic-onset juvenile idiopathic arthritis (SJIA) [6567].…”
Section: Anti-inflammatory Cytokine Biologicsmentioning
confidence: 99%
“…Thus, better treatments for rheumatoid arthritis and disorders of pyrin-associated pathways (e.g., familial Mediterranean fever and related disorders) utilizing biologics targeting either cytokines or their receptors have markedly reduced the incidence of AA as a consequence of these conditions. [122][123][124] The apparent uniqueness of the process of amyloidogenesis related to TTR deposition, in which the monomer aggregation precursor concentration is increased in the absence of increased synthesis or aberrant processing (J. Kelly, this volume), has allowed TTR-specific approaches to therapy and possible prophylaxis. Since 1990, the standard therapy for this disease has been liver transplantation.…”
Section: The Application Of Molecular Insights To Therapy (1975 Onward)mentioning
confidence: 99%
“…In a very recent period of time, it has been reported that it is effective on the treatment of several human inflammatory disorders, such as Mevalonate kinase deficiency (MKD)[18], systemic juvenile idiopathic arthritis (SJIA) [1921], TNF receptor-associated periodic syndrome (TRAPS) [22], refractory chronic tophaceous gout [23], and refractory adult-onset Still’s disease [13], Schnitzler syndrome [24], cryopyrin-associated periodic syndromes [25], refractory Sweet’s syndrome [26], autoinflammatory Muckle–Wells syndrome [27], persistent knee effusion [28], familial Mediterranean fever [29], Castleman’s disease [30], and arthrofibrosis [31]. …”
Section: Il-1 Receptor Antagonist Human Diseases and Pharmaceutimentioning
confidence: 99%